2011
DOI: 10.1016/j.exphem.2011.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 overexpression is regulated by signaling through PI3K, AKT2, and mTOR in imatinib-resistant chronic myeloid leukemia cells

Abstract: Objective. As a better understanding of the molecular basis of carcinogenesis has emerged, oncogene-specific cell-signaling pathways have been successfully targeted to treat human malignances. Despite impressive advances in oncogene-directed therapeutics, genetic instability in cancer cells often manifest acquired resistance. This is particularly noted in the use of tyrosine kinase inhibitors therapies and not more evident than for chronic myeloid leukemia. Therefore, it is of great importance to understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 52 publications
0
32
0
1
Order By: Relevance
“…Consistently, interference with SphK1 activity by dominant-negative mutants or competitive inhibitors such as N,N-dimethylsphingosine (DMS), as well as inhibition of S1P by mAbs or S1P receptors antagonists such as fingolimod (FTY720, Novartis), blocks tumorigenesis and tumor angiogenesis in cancer models (8). Moreover, recent studies showed that alterations of ceramide/S1P rheostat may be involved in the regulation of resistance to both chemotherapeutics and targeted agents (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Consistently, interference with SphK1 activity by dominant-negative mutants or competitive inhibitors such as N,N-dimethylsphingosine (DMS), as well as inhibition of S1P by mAbs or S1P receptors antagonists such as fingolimod (FTY720, Novartis), blocks tumorigenesis and tumor angiogenesis in cancer models (8). Moreover, recent studies showed that alterations of ceramide/S1P rheostat may be involved in the regulation of resistance to both chemotherapeutics and targeted agents (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 92%
“…On the basis of the evidence that alterations of ceramide/ S1P rheostat may be involved in resistance to biologic agents (9,13,14) and as some reports showed cross-talks between SphK1 and EGFR-dependent pathways (15,16,31), we investigated the role of SphK1 in the onset of resistance to cetuximab in colorectal cancers. To this aim, we analyzed SphK1 expression and activation in preclinical models of colorectal cancer, both sensitive or with intrinsic/ acquired resistance to cetuximab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, raised SphK1 has been associated with chronic myeloid leukemia resistance to imatinib and pancreatic cancer cell resistance to gemcitabine (16,25). Conversely, SphK1 inhibition can sensitize CML and pancreatic cancer cells to the proapoptotic effects of gemcitabine and imatinib, respectively, apparently by increasing the ceramide/S1P ratio and thereby enabling C18-ceramide-dependent apoptosis to proceed (16,25). Moreover, blockade of the SphK1 signaling pathway may reprogram cellular responsiveness to tamoxifen and abrogate antiestrogen resistance in human breast cancer cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cancer cells, tumors contain a repertoire of recruited ostensibly normal cells that contribute to cancer biology by creating the tumor microenvironment. Cancer cells do not manifest the disease alone, but rather conscript and corrupt resident and recruited normal cells, and collaborative ( 31 ), colon ( 34,35 ), breast ( 36,37 ), prostate ( 38 ), nonHodgkin's lymphoma ( 39 ), chronic myeloid leukemia ( 40 ), astrocytoma ( 41 ), and glioblastoma ( 42 ). In several of these studies, increased SphK1 expression correlated with increased tumor grade and poor prognosis.…”
Section: S1p and Its Roles In Cancermentioning
confidence: 99%